INCIDENCE AND ROOT CAUSE OF UPCODING IN THE IMPLEMENTATION OF SOCIAL HEALTH INSURANCE IN RURAL PROVINCE HOSPITAL IN INDONESIA - Syafrawati Syafrawati; Rizanda Machmud; Prof. Syed Mohammed Aljunid; Rima Semiarty (Asia Pacific Fraud Journal, 2020)
Upcoding is one of important indicators of moral hazard and fraud in Social Health Insurance scheme. However, there seems to be little evidence about incidence of upcoding and how upcoding occurs in hospital, especially in rural province hospital. The objective of this study is to determine incidence and root cause of upcoding in the implementation of Social Health Insurance in Rural Province Hospital in Indonesia. The data used in this study were both qualitative and quantitative data (mixed method). Three hundred and sixty (360) inpatient medical records from six rural province hospitals were examined in this study. Diagnosis and procedure codes recorded in these medical records were re-coded by an independent senior coder (ISC). Codes from hospitals’ coders and codes from ISC were then re-grouped using INA-CBG casemix grouper to determine the casemix groups and the hospital tariffs. If the hospital tariff obtained by hospital coder is higher than that obtained by ISC, it is considered as upcoding. This qualitative study was conducted using Focus Group Discussion (FGD) and in-depth interviews in hospitals located in a rural province of Indonesia. In depth interview was held for two hospital directors and two officers from the Social Security Administrator (Indonesia: BadanPenyelenggaraJaminanSosial/BPJS), an agent that manages the Statutory Health Insurance (SHI). Six clinicians and six coders attended the FGD. We asked open-ended questions about their perceptions on upcoding in hospitals. The interviews were recorded and transcribed verbatim. The transcripts were then thematically analyzed. Upcoding cases were found in 11.9% (43/360) medical records. Upcoding cases were dominated by Deliveries Group 2.8% (10/360) and Female reproductive system Groups 1.7% (6/360). The potential loss of income due to upcoding was IDR 154.626.000 or 9% of hospital revenue. Appointment of non-medical doctors as internal verifiers, lack of clear coding guidelines, lack of training for doctors and coders, and poor coordination between hospital and BPJS to resolve coding disagreement were root causes of upcoding in hospital. Policies to prevent and manage upcoding should be urgently developed and implemented in the Statutory Health Insurance (SHI) program in Indonesia especially to prepare upcoding guidelines, enhance medical coding trainingregularly, increase number of coders and verification staff from medical background, and strengthen coordination for coding problem solving in hospital.